P149 Evolution of the NCSP: Integrating chlamydia screening into community health services; policy and practice developments in England. (23rd May 2012) - Clarke, J; Bone, A
Abstract : Background: The National Chlamydia Screening Programme is a major component of sexual health provision in England. Over 1.4 million tests were performed on asymptomatic under 25-year olds in 2010/2011, and over 87 000 diagnoses made. The expansion of chlamydia testing services in the NHS has occurred predominantly outside of GUM utilising both traditional health services and introducing alternative approaches for young people to access testing. Coverage of screening has been higher in deprived areas and among young people at increased risk of infection. Discussion: The NCSP is evolving from a stand-alone programme to one that is integrated in primary care and sexual health services, with outreach screening being restricted to hard to reach groups. This integration is occurring both in terms of the way chlamydia screening is commissioned and provided, and in terms of data collection, removing the requirement for chlamydia-specific services. This process is expected to substantially improve value for money and maximise synergies between chlamydia prevention and other services. Clinical research and modelling, comparison with other programmes around the world and the major organisational changes in the NHS and public health system continue to shape the commissioning and delivery of screening. Clinical practice, from distribution of test kits to partner notification and treatment, is increasingly dependent upon electronic resources. Key discussion points include: How can we continue to develop flexible, responsive community sexual health services that include chlamydia screening as a core component? Will evaluation criteria for quality assurance and for clinical effectiveness currently applied to a stand-alone NCSP be valid in the integrated models?